Penerapan Algoritma Booyer Moore Pada Aplikasi Teka Teki Silang (TTS) - Ramadhan, M. Ibnu (TIN: Terapan Informatika Nusantara, 2021)
Crossword or abbreviated with TTS is a game to fill the empty spaces (in the form of white boxes) with letters that form a word based on the instructions given. In further developments, this puzzle is also intended for problems that must be filled with numbers. To fill in the letters in each box, instructions are given that are divided into "horizontal" and "downward" categories. The speed at which to play the crossword game depends greatly on the vocabulary possessed by the player. That is because the game must be able to arrange words whose letters are interrelated arranged vertically and vertically, the words must be in accordance with the theme of questions provided by the game. Boyer Moore's algorithm is the most efficient string search algorithm and has become the standard of the string search system. This algorithm detects patterns in strings by comparing characters in different sequences. This process is called Shift, and shift rules are calculated by applying 2 rules, namely bad character rules and good suffix rules. The maximum value of the shift length that can be done is calculated by this rule, then the character search is carried out from the beginning until the shift is as long as the shift length